Impact of COVID-19 in the stock market: volatility spillover - Silva, Bruno Daniel Pinto Ruivo da (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management